A Blockchain-Based Framework for Secure and Transparent Environmental Data Sharing in Smart Cities: Enhancing Trust, Integrity, and Interoperability in Urban Sustainability Systems - Turan, Mohammad Nawab; Hashimzai, Irshad Ahmed; Qiam, Mohammad Qaseem (Universitas Pendidikan Nasional, 2025)
Blockchain technology has emerged as a transformative tool to address critical challenges in environmental data management within smart cities, particularly enhancing trust, data integrity, and interoperability. This systematic literature review aims to analyze how blockchain frameworks support secure and transparent environmental data sharing for sustainable urban development. The study involved a comprehensive search of multiple academic databases, including IEEE Xplore, ScienceDirect, Wiley, and MDPI, covering publications from 2019 to 2025. A total of 23 relevant papers were selected and critically examined. The results reveal that blockchain-based solutions often integrate with emerging technologies such as artificial intelligence and digital twins to improve data validation, governance, and real-time analytics. Key innovations include decentralized trust frameworks, smart contract governance, and interoperability models like Blockchain-of-Blockchains. Despite these advancements, challenges such as scalability, energy consumption, and lack of standardization persist. The review concludes that while blockchain offers a robust foundation for secure and interoperable environmental data systems in smart cities, ongoing research and collaboration are essential to overcome current limitations and achieve sustainable, transparent urban ecosystems.